Genocide and resistance Nr. 37(1) - Buchaveckas, Stanislovas; Rukšėnas, Alfredas; Vaiseta, Tomas; Stravinskienė , Vitalija; Banionis, Juozas; Ereminas, Gintautas (Genocidas ir rezistencija, 2015)
Full Issue